Celebrating every learner : activities and strategies for creating a multiple intelligences classroom - Hoerr, Thomas R.; Boggeman, Sally; Wallach, Christine (New York : Jossey-Bass, 2010)
Howard Gardner's groundbreaking theory applied for classroom use This important book offers a practical guide to understanding how Howard Gardner's theory of Multiple Intelligences (MI) can be used in the classroom. Gardner identified eight different types of intelligence: linguistic, logical, spatial, musical, bodily-kinesthetic, naturalist, interpersonal, and intrapersonal. Celebrating Every Learner describes the characteristics of each type of intelligence and follows up with ready-to-use lesson plans and activities that teachers can use to incorporate MI in their pre-K through 6 classrooms.-Offers a treasury of easily implemented activities for engaging all students' multiple intelligences, from the New City School, a leading elementary school at the forefront of MI education -Provides ready-to-use lesson plans that teachers can use to incorporate MI in any elementary classroom -Includes valuable essays on how and why to integrate MI in the classroom -Hoerr is the author of a bi-monthly column for Educational Leadership as well as the editor of the "Intelligence Connections" e-newsletter.
Includes bibliographical references and index.
Keywords: Elementary school teaching; Multiple intelligences; Cognitive styles; Learning; Interdisciplinary approach in education; Education -- Curricula